2017
DOI: 10.3892/or.2017.5606
|View full text |Cite
|
Sign up to set email alerts
|

A ligand-based and enediyne-energized bispecific fusion protein targeting epidermal growth factor receptor and insulin-like growth factor-1 receptor shows potent antitumor efficacy against esophageal cancer

Abstract: Abstract. Recent studies have revealed that the epidermal growth factor receptor (EGFR) and insulin-like growth factor-1 receptor (IGF-1R) are overexpressed in various types of human tumors and are attractive targets for anticancer drugs. In the present study, the expression of EGFR and IGF-1R in esophageal squamous cell carcinoma (ESCC) and adjacent normal tissues in a tissue microarray was firstly detected by immunohistochemical staining. In addition, their co-overexpression was observed in 48 out of 75 (64%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…As a classical intracellular signaling pathway, the PI3K/AKT pathway is activated by insulin signaling and regulates cell growth, apoptosis, and metabolism 49,50 . Many studies have proved that inhibiting IGF1R and PI3K/AKT can effectively prevent the malignant biological behavior of ESCC, and improve the treatment sensitivity 51–53 . Furthermore, this pathway has also been implicated in the generation of blood vessels and lymphatic vessels in a variety of tumors 54,55 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a classical intracellular signaling pathway, the PI3K/AKT pathway is activated by insulin signaling and regulates cell growth, apoptosis, and metabolism 49,50 . Many studies have proved that inhibiting IGF1R and PI3K/AKT can effectively prevent the malignant biological behavior of ESCC, and improve the treatment sensitivity 51–53 . Furthermore, this pathway has also been implicated in the generation of blood vessels and lymphatic vessels in a variety of tumors 54,55 .…”
Section: Discussionmentioning
confidence: 99%
“… 49 , 50 Many studies have proved that inhibiting IGF1R and PI3K/AKT can effectively prevent the malignant biological behavior of ESCC, and improve the treatment sensitivity. 51 , 52 , 53 Furthermore, this pathway has also been implicated in the generation of blood vessels and lymphatic vessels in a variety of tumors. 54 , 55 To verify whether the IGF1R/PI3K/AKT pathway mediates the regulation of ESCC lymphangiogenesis by miR‐100‐5p in CAF‐derived exosomes, we detected IGF1R, PI3K, AKT, and p‐AKT expression in TLECs and tumors.…”
Section: Discussionmentioning
confidence: 99%
“…ACAT-1 may increase cholesterol ester levels and elevate blood sugar in the body, resulting in insulin secretion which may in turn increase the activity of insulin-like growth factor (IGF). Increased IGF function may promote cell mitosis, thereby accelerating cell proliferation and promoting tumor growth (3032). Studies have demonstrated that IGF is closely associated with lung cancer progression (33,34).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, based on their highly consistent co-expression profile, the approach of dual inhibition of IGF1R and EGFR/HER2 was adopted and have shown significant success in multiple pre-clinical models of different cancer -viz. (i) a bi-specific (anti-IGF1R and -EGFR) antibody XGFR in pancreatic cancer (Schanzer et al 2016), (ii) IGF1R inhibitor linsitinib with EGFR inhibitors lapatinib or gefitinib in esophageal squamous cell carcinoma (Kang et al 2022), (iii) a ligand-based enediyne-energized bi-specific fusion protein (anti-IGF1R and -EGFR) in esophageal (Cao et al 2017) and non-smallcell lung cancer (Guo et al 2017), (iv) AVE1642 (anti-IGF1R mAb) and gefitinib in HCC (Desbois-Mouthon et al 2009), (v) ganitumab and panitumumab (anti-EGFR mAb) in advanced cancers (non-small-cell lung cancer and sarcoma) (Vlahovic et al 2018) Endocrine-Related Cancer e220414 and panitumumab in metastatic colorectal cancer (Van Cutsem et al 2014), to name a few. Interestingly, the antidiabetic 'wonder drug' metformin is reported to affect a downregulation of IGF1R and thereby enhance the efficacy of figitumumab (mAb against IGF1R) in smallcell lung cancer (Cao et al 2015) and non-small-cell lung cancer (Cao et al 2016).…”
Section: Gh and Igf1 In Cancer-targeted Therapy Responsementioning
confidence: 99%